2021
DOI: 10.5430/wjss.v8n1p104
|View full text |Cite
|
Sign up to set email alerts
|

Cyber Child Abuse in Bangladesh: A Rural Population-Based Study

Abstract: Background: Cyber abuse has become common among children worldwide; however, it is yet to receive attention in Bangladesh. The present study aimed to determine the prevalence and associated risk factors of cyber child abuse in the context of Bangladesh. Methods: This population-based study was conducted on 460 children aged between 11 to 17 years recruited from a selected rural area of Bangladesh by simple random sampling. A cyber abuse scale was developed to measure the prevalence of cyber child abuse. Data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…4 Among the psychological risk factors, depressive symptoms, low self-esteem, anti-social behavior, and emotional immaturity were significant contributors. 14 According to the study conducted by Salwa et al, the odds of being sexually abused online for urban children was double that for rural in Bangladesh, while every additional hour of internet use per day increased the chance of being sexually abused online by a factor of 1.09. Moreover, navigating to more social media sites and greater internet device usage increase the likelihood of online child sexual abuse.…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Among the psychological risk factors, depressive symptoms, low self-esteem, anti-social behavior, and emotional immaturity were significant contributors. 14 According to the study conducted by Salwa et al, the odds of being sexually abused online for urban children was double that for rural in Bangladesh, while every additional hour of internet use per day increased the chance of being sexually abused online by a factor of 1.09. Moreover, navigating to more social media sites and greater internet device usage increase the likelihood of online child sexual abuse.…”
Section: Risk Factorsmentioning
confidence: 99%
“…13 Mubassara et al, in their study, found that about 21% of rural children in Bangladesh reported that they received sexually explicit messages, and 17% reported receiving videos or pictures with sexual content. 14 Newspaper reports also show a considerable number of children getting exposed to unpleasant online experiences. 15 A recent study found that 86% female and 91% male children of Bangladesh use the internet where the most common pattern of abusive events include receiving vulgar friendship request from unknown persons (47%), online sexual propositions (35%), receiving pornographic texts or audios (29%), receiving pornographic videos (29%), requests for inappropriate images or videos (19%), and requests to send naked or half-naked images or videos (18%).…”
Section: Prevalence In Bangladeshmentioning
confidence: 99%
“…It is presumed that young children and senior citizens are less capable of self-defense and are unaware of possible recourse for them to keep themselves safe from such danger, the same is true in case of women who may not possess the physical strength to defend themselves in such situations. [2] Violence against women and children has emerged as a significant and growing concern worldwide. To avoid violence, various machine learning (ML) approaches could be used to estimate future violence.…”
Section: Introductionmentioning
confidence: 99%
“…A UNICEF survey conducted in 2019 showed that around 32% of children aged 10À17 years in Bangladesh face cyberbullying and cyber harassment (Nabi, 2019;UNICEF, 2019). More recently, Mubassara et al (2021) revealed that around 21% of rural children in Bangladesh received sexually explicit messages, while 17% received videos or pictures with sexual content. Available evidence further indicates that 56% of male and 64% of female children in Bangladesh face online sexual abuse (Ain o Salish Kendra, 2023).…”
Section: Introductionmentioning
confidence: 99%